Midline catheter (10 cm) versus long peripheral intravenous catheter (6.4 cm): Randomized clinical trial protocol with economic analysis - Tiago Oliveira Teixeira; Leandro Augusto Hansel; Rodrigo do Nascimento Ceratti; Ivana Duarte Brum; Arlene Gonçalves dos Santos Fernandes; Carolina Geske Saline; Marina Junges; Eneida Rejane Rabelo-Silva (PLoS ONE, 2025)
Introduction Midline catheters have stood out in the last decade in Europe and North America as peripheral venous access devices with fewer complications and greater durability. However, its cost may be an obstacle to the adoption of this technology in public institutions in Brazil, which use long peripheral intravenous catheters for the same purpose. Materials and Methods This is a randomized clinical trial protocol, registered on the ClinicalTrials.gov NCT05884294 platform, which will be conducted with two parallel, controlled, single-center, blinded groups for outcome analysis, where the groups are allocated in a 1:1 ratio, with patients over 18 years of age, admitted to clinical units of a public university hospital in Brazil who have difficult venous access defined by the Adult Difficult Intra Venous Access Scale (A-DIVA). The study intervention will be the insertion of a PowerGlide ProTM Midline 20G catheter (10 cm). The control group will receive an Introcan Safety Deep Access long peripheral intravenous catheter 20G (6.4 cm). The primary outcome will be the length of stay of vascular access free of complications (infiltration, phlebitis, occlusion, accidental withdrawal, catheter-associated bloodstream infection, and deep vein thrombosis). The economic analysis will follow micro-costing. Objective To compare the use of the midline catheter (10 cm) in terms of the length of stay free of complications with the use of a long peripheral intravenous catheter (6.4 cm) during continuous or intermittent intravenous therapy for more than five days in adult clinical patients, with difficult venous access, hospitalized in a public institution in Brazil. It also aims to carry out an economic analysis based on micro-costing. Conclusion The international literature, especially in North America and Europe, has shown that the use of midline catheters and long peripheral intravenous catheters have similarities regarding greater safety and lower risk of complications. The superiority related to the midline catheter in terms of the time of uncomplicated use in patients in need of peripherally appropriate solutions, but with high cost, is highlighted. The use of these devices remains incipient in Latin America, especially in Brazilian public institutions, requiring studies to evaluate evidence on the use and costs of these technologies in this specific population. Trial Registration: ClinicalTrials.gov. NCT05884294